Performance evaluation of rigid braced indirect suspended ceiling with steel panels - Lee, Jae Sub; Jung, Dam I.; Lee, Doo Yong; Cho, Bong Ho (Applied Sciences (Switzerland), 2021)
In Korea, the earthquakes in Gyeongju (2016) and Pohang (2017) have led to increased interest in the seismic design of nonstructural elements. Among these, the suspended ceiling can cause personal injury and property damage. In addition, most suspended ceilings that are used in Korea neither have seismic design details nor meet the current seismic design standards. There are two seismic design methods for suspended ceilings using a perimeter clip and a brace. In the United States and Japan, seismic design of ceilings is typically used, but the concepts of applying and installing braces are different. This is because the typical ceiling systems are different in the United States and Japan. In this study, a brace-applied ceiling system that is suitable for a suspended ceiling with a steel panel was applied in the indirect suspended ceiling mainly used in Korea. In addition, the seismic performance was verified through a shaking table test. All the specimens were applied with anti-falling clips that are designed to prevent the panels from falling, and they satisfy KDS 41 17 00, which is a Korean seismic design life safety standard. Without considering these factors, the performance level is lower than a nonseismic designed ceiling, which is not properly designed or constructed.
Keywords: Nonstructural element; Rigid brace; Seismic design; Seismic performance; Shaking table test; Suspended ceiling